Modernidad colonial: la dimensión patrimonial de la metrópoli - Campos-Salas, Jeannette (2012)
This article makes questions about the traditional vision or perception of modernity and propose to make a new analysis or study about the colonial modernity, that is developed at the same time and in an opposite and exertion way of the metropolitan modernity. In the context of Latin America this analysis means to understand the conquest and the european ocupation of our continent like a part of the first wave of modernity and like the place where the first conceptions of race, humans natural differences and tipical hierarchys of modern structures of domination.